2018
DOI: 10.1371/journal.pone.0206943
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medication adherence on disease activity among Japanese patients with rheumatoid arthritis

Abstract: For the optimum efficacy of disease-modifying anti-rheumatic drugs (DMARDs), patients need to be adherent to their medication regimen. To clarify the effects of medication adherence on disease activity in Japanese patients with rheumatoid arthritis (RA), we conducted a cohort study in patients with various stages of RA. Patients were enrolled from the Kyoto University RA Management Alliance cohort, and followed up prospectively for 12 months. In this study, a total of 475 patients were analyzed and divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
2
9
0
1
Order By: Relevance
“…Accordingly, it was determined that as the continuity of care and the treatment adherence increased, the functionality increased, and as the disease activity increased, the functionality decreased. Similarly, studies conducted by Ragab et al, 70 Pascual-Ramos et al, 71 and Nakagawa et al, 72 it was found that functionality increased as the treatment adherence increased. Studies conducted by Drossaers-Bakker et al, 73 Sokka et al, 74 Boyd et al, 75 Nikiphorou et al, 76 and Kamel et al 77 it was determined that there was a negative relationship between the disease activity and the functionality.…”
Section: Discussionmentioning
confidence: 59%
“…Accordingly, it was determined that as the continuity of care and the treatment adherence increased, the functionality increased, and as the disease activity increased, the functionality decreased. Similarly, studies conducted by Ragab et al, 70 Pascual-Ramos et al, 71 and Nakagawa et al, 72 it was found that functionality increased as the treatment adherence increased. Studies conducted by Drossaers-Bakker et al, 73 Sokka et al, 74 Boyd et al, 75 Nikiphorou et al, 76 and Kamel et al 77 it was determined that there was a negative relationship between the disease activity and the functionality.…”
Section: Discussionmentioning
confidence: 59%
“…В одній із недавніх робіт S. Nakagawa та співавт. [11] показали, що хворі з високою прихильністю мають значно нижчу активність ПсА, проте ця закономірність поширюється тільки на пацієнтів з три-валістю ПсА до 4,6 років. За більшої тривалості захворювання такої залежності не відзначається.…”
Section: результати дослідження та їх обговоренняunclassified
“…According to several studies in RA patients, higher medication adherence is statistically significant associated with lower flare rate and disease activity score (DAS-28). [4,5] Effective disease control at an early stage can also prevent irreversible joint damage and hence improve patients' quality of life. [4] Study data also supported that drug counseling and education has the highest evidence in improving medication adherence.…”
Section: According To a Study Conducted By Census And Statisticsmentioning
confidence: 99%
“…[4,5] Effective disease control at an early stage can also prevent irreversible joint damage and hence improve patients' quality of life. [4] Study data also supported that drug counseling and education has the highest evidence in improving medication adherence. [6] Pharmacists who are the experts in drugs are capable of providing counseling to arthritis patients, improving their drug adherence and disease activities.…”
Section: According To a Study Conducted By Census And Statisticsmentioning
confidence: 99%